Tribunais de Contas e controle de constitucionalidade de leis e atos normativos emanados do Poder Público - Favoretto, Danilo Galan (2016)
This work has as its main scope highlighting the subject related to the Brazilian Court of Auditors performance and its implications in the exercise of the constitutionality control of the legal rules issued by the Public Power. It seeks to define the role of Court of Auditors within the context in which it is inserted, in order to clarify any subject involving the constitutionality conformity exam of the administrative acts egarding the public management under its evaluation and, consequently, of the laws and normative acts that underlie them. Such study is dedicated, then, to the analysis of the Court of Auditors procedure mode before unconstitutional laws and administrative acts, particularly considering the extension of the attribution for such Court committed from 1988, examining the issue in the light of Constitution, the legal system, the doctrine and jurisprudence, given the importance that it takes for the Brazilian constitutionality control